Pengaruh Reward dan Punishment Terhadap Kinerja Karyawan : (Studi Kasus Pada Karyawan Perusahaan Agrowisata Nabila Farm Lembang) - Safitri, Risky Nadila; Nurjanah, Suci; Roisah, Riris (Fakultas Ekonomi dan Bisnis, 2024)
This research aims to find out how reward and punishment affects employee performance at the Nabila Farm Lembang agrotourism company. The testing technique used is quantitative with the number of samples taken from the entire employee population of twenty employees. The information sources utilized within this research are essential data acquired from the survey. Before testing the hypothesis, the multiple regression model is first tested with classical assumptions to ensure that the data is feasible for hypothesis testing. The analytical instrument used is Microsoft Excel software and SPSS 25. The results of this research showed that partially reward and punishment affected employee performance at the Nabila Farm Lembang agrotourism company. Simultaneously, reward and punishment affected employee performance.